Les différents cercles de protection autour de Louis XIV - Rémi Masson (Bulletin du Centre de Recherche du Château de Versailles)
The reforms undertaken by Louis XIV from the beginning of his personal government enabled the king to establish himself throughout his reign as the true master of his Military Household. The sovereign succeeded in transforming units that sometimes operated in an archaic fashion into a guard capable of offering effective protection, while at the same time being a parade corps that played a full part in the spectacle of absolutism. This meant structuring these units around an efficient domestic service, capable of meeting the challenges of the King’s over-exposure to the public. Like the orbit of the planets around the Sun King, the service provided by the corps of the Military Household manifested as a series of concentric circles around the sovereign that complemented each other to effectively ensure his protection in all contexts. As well as guaranteeing the sovereign’s security, the Military Household became a veritable tool for representing absolutism, playing a role of pomp and ceremony that had never been seen before. To meet this challenge, its numbers were increased and its training and discipline improved. At the same time, these reforms enabled the troops of the King’s Household to become more professional and to be structured as a true military institution.